Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1158/1541-7786.mcr-19-0718
|View full text |Cite|
|
Sign up to set email alerts
|

OLR1 Promotes Pancreatic Cancer Metastasis via Increased c-Myc Expression and Transcription of HMGA2

Abstract: Pancreatic cancer is one of the most lethal human malignancies, partly because of its propensity for metastasis. However, the mechanisms of metastasis in pancreatic cancer remain unclear. Oxidized low-density lipoprotein receptor 1 (OLR1), a lectin-like scavenger receptor that recognizes several ligands, such as oxidized low-density lipoprotein, was previously reported in cardiovascular and metabolic diseases. The role and mechanism of OLR1 in pancreatic cancer is unclear. In this study, we found that OLR1 exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…Recently, a study has deepened the pathway involved in LOX-1-induced-PC metastasis [ 58 ]. The whole transcriptome RNA-sequencing analysis of pancreatic adenocarcinoma cells in which OLR1 has been overexpressed or inhibited was performed.…”
Section: Lox-1 and Pancreatic Cancermentioning
confidence: 99%
“…Recently, a study has deepened the pathway involved in LOX-1-induced-PC metastasis [ 58 ]. The whole transcriptome RNA-sequencing analysis of pancreatic adenocarcinoma cells in which OLR1 has been overexpressed or inhibited was performed.…”
Section: Lox-1 and Pancreatic Cancermentioning
confidence: 99%
“…A previous study showed that OLR1 is a lectin-like scavenger receptor. This receptor binds to several ligands, such as oxidized low-density lipoprotein, polyanionic chemicals, and anionic phospholipids [ 47 ]. Aberrant expression of O LR1 has been reported in multiple cancers; its expression induces the release of inflammatory cytokines and is closely related to cancer development and metastasis [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, long noncoding RNA VPS9D1 antisense RNA 1 (VPS9D1-AS1) promotes HMGA2 expression by sponging miR-532-3p in non-small cell lung cancer (NSCLC) cells [31]. Oxidized low density lipoprotein receptor 1 (OLR1) increased HMGA2 transcription by upregulating c-Myc expression in pancreatic cancer cells [32]. However, the mechanism underlying which regulates the transcriptional expression of HMGA2 in hepatocellular carcinoma cells remains largely unclear.…”
Section: Discussionmentioning
confidence: 99%